Drugs and human behavior - Palfai, Tibor (Brown & Benchmark, 1997)
Drugs and Human Behavior provides unique historical background and introduces students to psychoactive drugs' pharmacology and the mental illnesses they are used to treat. This text is ideal for upper-level courses that take a psychopharmacological approach (rather than a social or health approach) and emphasize practical applications.